Budaya Kerja Dan Kualitas Kerja Di PT. Bank Maluku Malut Cabang Tobelo - Vebrianti Bitikal; Anita Dilly; Oktadwilaras Anugerah Putri Papuling (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2025)
This research aims to determine work culture and the impact of work culture towards employee’s work quality at PT Bank Maluku Malut, Tobelo branch. This research uses descriptive qualitative methods. Data was obtained through interviews with 5 (five) research informants. The research results are then researched, analyzed, developed and adapted to supporting theories. The research results show that work culture as a reference, values, work design, work systems and organizational environment are things that need to be considered in efforts to achieve optimal employee work quality. Because, optimal employee work quality will have an impact on increasingly optimal organizational performance. The impact of work culture on work quality can be seen from 2 (two) sides, namely First, from the positive side, namely that it can improve the quality of employee work. Second, from the negative side, namely the occurrence of fraud or banking crime. Banking crimes can occur if employees misuse their skills at work for things that can harm themselves and the company. The role of organizational leaders is needed to encourage employee behavior in increasing work morale, working more structured, minimizing boredom at work and increasing work discipline.